Analyzing the Maduranese's Traditional Inheritance from al-Tūfi’s Maslahah Theory - Maimun, Maimun; Harisah, Harisah; Hanafi, Imam; Sulaiman, Zubaidi (al-'adalah, 2021)
This study reveals the tradition of inheritance distribution among the Maduranese community and analyzes it using the maslahah of al-Tūfi. Although the entire Maduranese community adheres to Islam, in terms of inheritance distribution, they tend to apply customary inheritance law, only a small portion of which applies Islamic inheritance law (farāidh). This research is qualitative research; the data is obtained from interviews, observations, and documentation. This study found that most Maduranese people only give inheritance portion to children's groups, rarely did they include other groups as stipulated in farāidh law. Apart from that, the distribution pattern is also different from one region to another. In Sumenep, for instance, the distribution of inheritance prioritizes girls over boys. In Sampang, priority is given to the eldest child, while in Bangkalan it is prioritized for the youngest child. Only in Pamekasan, the distribution of inheritance is distributed to all family members in equal portions. This pattern of distribution that does not comply with the provisions of Islamic inheritance law, when viewed from the perspective of maslahah al-Tūfi, is still in line with the principles of Islamic law because it aims to bring good, avoid conflict, as well as to adjust to customary provisions and community development.